2013
DOI: 10.1080/09687599.2012.714257
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the social geographies of autism – online and off-line narratives of neuro-shared and separate spaces

Abstract: 1Mapping the social geographies of autism -on-and off-line narratives of neuro-shared and separate spaces Points of Interest •We use the term 'space' to mean the places where people can talk with each other and meet. Spaces can either be accessible or not for people with autism.• On-line spaces are where people meet and talk through the internet. Research has shown that on-line spaces can be a helpful way for people with autism to communicate.• Off-lines spaces are where people meet face to face. Off-line spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Our previous work has indicated that spaces that respect neurodiversity can be created and managed by people with autism in order to facilitate friendships and close relationships (see for example Bertilsdotter Rosqvist, Brownlow, and O'Dell 2013). Given the possibilities for the formation of neurodiverse spaces online, there is a need for research that documents the alternative forms that 'friendship' may take for people with autism in contexts that feel safe and supportive.…”
Section: Proposing Alternative Understandings Of (Autistic) Friendshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has indicated that spaces that respect neurodiversity can be created and managed by people with autism in order to facilitate friendships and close relationships (see for example Bertilsdotter Rosqvist, Brownlow, and O'Dell 2013). Given the possibilities for the formation of neurodiverse spaces online, there is a need for research that documents the alternative forms that 'friendship' may take for people with autism in contexts that feel safe and supportive.…”
Section: Proposing Alternative Understandings Of (Autistic) Friendshipmentioning
confidence: 99%
“…Neurodiverse spaces may be online communities or face-to-face environments that are designed to be accessible to both NTs and people with autism (Bertilsdotter Rosqvist, Brownlow, and O'Dell 2013). An alternative version of friendships, accessed often through the narratives of people supposedly lacking the ability to have and make friends provides us with a valuable insight into a richer and more diverse understanding of friendships.…”
Section: Proposing Alternative Understandings Of (Autistic) Friendshipmentioning
confidence: 99%
“…Given the tendency to avoid large groups, unfamiliar spaces, and social situations, the Internet has facilitated the growth of group identity and solidarity (Biever, 2007;Brownlow and O'Dell, 2006;Davidson, 2008). In virtual spaces, autistic people informed by critical disability studies reframe their difference as one of many forms of human neurodiversity (Bertilsdotter Rosqvist et al, 2013), and problematize the hegemony of neurotypical, and increasingly also, gender norms.…”
Section: Autism From the Insidementioning
confidence: 98%
“…Using technology allows the user to insert themselves into various situations, no matter where the user is physically. Additionally, technologies that support nonverbal skills can build a bridge between the normative and neurodiverse experiences, which some researchers refer to as "neuro-shared spaces" (9).…”
Section: Introductionmentioning
confidence: 99%